Change to strange create a great organization by building a strange workforce - Cable, Daniel M. (Wharton School Pub., 2007)
"This book is about everything it takes to build a workforce that's strange and extraordinary enough to execute your most powerful strategies and your unique value proposition. It's about understanding exactly how your workforce needs to be different; creating an end-to-end Strange Workforce Value Chain; implementing workforce systems that support your unique goals; and establishing detailed metrics based on what makes you unique, using those metrics to drive clarity throughout your entire organization, and steer it toward success."--Jacket
Includes index. - Includes bibliographical references and index. - Print version record
Keywords: Organizational effectiveness; Efficacité organisationnelle